Chromatographic profiling of Pancharishta at different stages of its development using HPTLC, HPLC, GC–MS and UPLC–MS. (June 2017) - Khan, Washim; Chester, Karishma; Anjum, Varisha; Ahmad, Wasim; Ahmad, Sayeed; Narwaria, Avinash; Kumar, Das Prasanta; Katiyar, C.K.
Graphical abstract: Highlights: Stepwise preparation of an important Ayurvedic Pancharishta formulation as per traditional claims. Quality control evaluation of different Pancharishta formulations by HPTLC and quantitative differentiation by HPLC. Metabolic discrimination of different Pancharishta formulation through UPLC–MS and GC–MS. Describing the statistical correlation among different Pancharishta formulation. Abstract: Pancharishta is the traditional Ayurvedic polyherbal formulation prepared by decoction of plant materials followed by fermentation for preservation and facilitation of extraction due to the production of alcohol. Since the preparation of pancharishta involves various steps. The aim of the current investigation was to carry out comparative metabolomics profiling at different stages of preparation for the understanding impact of different steps and ingredients. A decoction of 21 plant materials are main components in pancharishta formulations followed by fermentation and addition of other ingredients with or without fermentation yielded eight different formulations. The vacuum concentration of pancharishta samples yielded a semisolid mass of different formulations ranging from 8 to 37% w/v. The HPTLC fingerprinting analysis of samples was carried out in butanol: ethanol: 0.5% v/v ammonia (5:4:0.5, v/v/v ). Derivatization with anisaldehyde-sulphuric acid showed the presence of two major peaks at Rf 0.29 and 0.35. The peak at Rf 0.29 is intense in a formulation containing 12 extra plant materials. Quantification of gallic acid, ellagic acid, tannic acid, kaemferol and quercetin were carried out on newly developed HPLC method using acetonitrile and 0.5% v/v formic acid with a gradient elution. A significant difference in their content was found in different formulations. Further, polar and nonpolar metabolites of pancharishtha were analyzed using UPLC–MS and GC–MS, respectively. GC–MS profiling results in the identification of 144 metabolites among them 26 are common metabolites at different stages. The UPLC–MS analysis resulted in the tentative identification of 43 metabolites. The results of UPLC–MS and GC–MS analysis were used for multivariate analysis using XLSTAT. Principal Component Analysis plot distributed all samples into four different clusters with two formulations each.